Cobalt and nickel selenide nanowalls anchored on graphene as bifunctional electrocatalysts for overall water splitting. Issue 38 (15th September 2016) - Li, Xiao; Zhang, Li; Huang, Meirong; Wang, Shuying; Li, Xinming; Zhu, Hongwei
Abstract : Co and Ni based selenide nanowalls have been prepared on a conductive graphene coated nickel mesh substrate and used as electrocatalysts for hydrogen generation and oxygen evolution. The bifunctional nanowalls manifest a low driven voltage and high structural stability for overall water splitting. Abstract : The development of efficient and low-cost solar-driven overall water splitting systems for sustainable hydrogen generation is still a challenge. Herein, cobalt and nickel (Co and Ni) selenide nanowalls have been prepared on a conductive graphene coated Ni mesh substrate and used as electrocatalysts for hydrogen generation and oxygen evolution. The bifunctional CoSe nanowalls showed a high electrochemically active surface area, which manifested a low onset potential and high structural stability for overall water splitting. It afforded a 10 mA cm −2 current density at −78 mV vs. RHE for the hydrogen evolution reaction and 150 mA cm −2 at 1.74 V vs. RHE for the oxygen evolution reaction. No significant degradation was observed after a 24 h chronoamperometric test. A solar water electrolysis system was constructed by connecting the CoSe (+) and CoSe (−) pair with a photovoltaic cell in tandem, which showed a highest solar-to-hydrogen conversion efficiency of 6.65%. Its superior performance over industrial water electrolyzers provided a new possibility towards clean energy storage and utilization.